2007
DOI: 10.3390/md20070014
|View full text |Cite
|
Sign up to set email alerts
|

Production of the Neurotoxin BMAA by a Marine Cyanobacterium

Abstract: Diverse species of cyanobacteria have recently been discovered to produce the neurotoxic non-protein amino acid β-methylamino-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 18 publications
1
51
1
1
Order By: Relevance
“…The first follow-up studies on cyanobacterial isolates and field samples confirmed the presence of BMAA in the majority of the tested samples, albeit at slightly lower concentrations than initially reported [34][35][36]. However, other laboratories could not detect BMAA in any cyanobacterial sample (e.g.…”
Section: Controversy Regarding the Presence Of Bmaa In Aquatic Ecosysmentioning
confidence: 71%
See 4 more Smart Citations
“…The first follow-up studies on cyanobacterial isolates and field samples confirmed the presence of BMAA in the majority of the tested samples, albeit at slightly lower concentrations than initially reported [34][35][36]. However, other laboratories could not detect BMAA in any cyanobacterial sample (e.g.…”
Section: Controversy Regarding the Presence Of Bmaa In Aquatic Ecosysmentioning
confidence: 71%
“…As BMAA does not contain a chromophore, most methods based on optical detection, such as liquid chromatography coupled to fluorescence detection (LC-FLD), require pre-column derivatisation with a chromophore containing reagent such as 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC, e.g. [34,96]). This pre-column derivatisation has an additional advantage: the derivatised molecule is bigger and more hydrophobic, which facilitates reversed phase LC separation.…”
Section: Analytical Methods For Bmaa Analysismentioning
confidence: 99%
See 3 more Smart Citations